On the origin of the November 23, 1969, Ozernoi tsunami in Kamchatka - Melekestsev I.V. (My University, 1995)
It is shown that the Ozernoi tsunami might be caused by a large slump on the continental slope of Kamchatka triggered by the November 23, 1969, M=7.7 earthquake that occurred at 57.8°N and 163.8°E. -from Journal summary
Keywords: 38.19.17 Землетрясения и сейсмотектоника